A Comparison of Adjectives in Persian and Arabic Languages (ادبیات تطبیقی, 2013)
Abstract Due to their correspondence with nouns−regarding function, number, gender, determinateness, and indeterminateness−adjectives in Arabic are distinct from adjectives in modern Persian. Unlike Arabic, adjectives in modern and ancient Persian are divided into two categories of preceding and following adjectives and, apparently, there is not any significant difference between adjectives and some other parts of speech like adverbs. In Persian, adjectives are recognized mainly according to syntactical features; in Arabic, however, both structure and syntax play important roles. One of the axiomatic topics in Persian grammar books is the fact that the correspondence between adjectives and nouns in Persian is taken from Arabic and it has never been a rule in Persian; however, constantly in ancient Persian and frequently in Iranian Mid-west Persian and Dari Persian, adjectives had been consistent with their corresponding nouns regarding number, gender and manner. This study tries, in the first step, to state some grammarians’ ideas and the history of adjective-noun correspondence. It also seeks to offer a general definition for adjectives both in Persian and Arabic and to compare them regarding lexis and syntax.